PENINGKATAN PRESTASI BELAJAR MATEMATIKA SISWA TUNANETRA MELALUI PEMBELAJARAN TEKNIK POLAMATIKA DI SLB-A YAPTI MAKASSAR - Marhani, Marhani (Pascasarjana Universitas Negeri Makassar, 2017)
Improving the learning achievement of students with visual impairment through learning the technique of polynesia is done in SLB-A yapti Makassar, data retrieval is done by using learning outcomes tests and observation sheets. The collected learning outcomes data were analyzed using quantitative analysis and observational data were analyzed by qualitative analysis. The results showed that the average score of students in cycle I was 57.5 from the ideal score of 100 increased in cycle II with an average score of 75 of the ideal score of 100. The average score increase was 17.5. In the first cycle, there are still 3 students who have not achieved mastery learning while the second cycle all students have achieved mastery learning. This shows that one of the existing indicators of success has been fulfilled, namely achieving a grade of at least 75%. From the results of this study it can be concluded that by using the technique of polynesia can improve the learning achievement of mathematics in students with visual impairments in SLB - A YAPTI Makassar.